A Model of the Costs for Tidal Range Power Generation Schemes. Issue 4 (15th November 2022) - Vandercruyssen, David; Howard, David; Aggidis, George
Abstract : Tidal range power is gaining recognition as a globally important power source replacing unsustainable fossil fuels and helping mitigate the climate change emergency. Great Britain (GB) is ideally situated to exploit tidal power but currently has no operational schemes. Schemes are large and expensive to construct, assessment of their costs is usually examined under conditions of commercial confidentiality. A national strategy for delivery needs a more open system that allows cost estimates to be compared between schemes; a model that evaluates the capital cost of major components has been developed. In 1983, Massachusetts Institute of Technology (MIT) published a simple additive model of the costs of tidal range schemes on the east coast of the USA. Their model has been updated and benchmarked against recent schemes with published costs; the Sihwa Lake Tidal Power Station (South Korea, completed in 2011) was used along with the published costs for the Swansea Bay Tidal Lagoon proposal in South Wales to benchmark the model. There are developments in civil and mechanical engineering that may influence both the costs and speed of deployment. These are discussed along with methods for their inclusion into the model. Highlights · Development of a cost model for tidal range schemes in the UK · Benchmarked against the Sihwa Lake Tidal Plant and Swansea Bay Tidal Lagoon proposal. · Cost estimation budgeted using 5-main elements · pre-cast concrete proposed for sluice gates, locks and barrages